A ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition and preparation method thereof

By developing a ceramic-based anti-sticking and anti-rust petroleum casing thread sealing grease composition, using zirconia ceramic-based high-temperature lubricating powder and other ingredients, the existing API thread grease can easily cause sticking under extreme pressure and high torque conditions. It solves the problem of buckles and achieves better anti-wear, lubrication, sealing and anti-rust properties.

CN116875358BActive Publication Date: 2025-01-21WUXI PETROCHINA LUBRICATING GREASE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310864518.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-21
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

The existing API thread grease has shortcomings in extreme pressure resistance, lubrication and friction reduction, rust resistance and sealing performance, especially in high torque oil drilling conditions, which can easily lead to casing thread clamping.

Method used

Develop a ceramic-based anti-sticking and anti-rust petroleum casing thread sealing grease composition, which uses zirconia ceramic-based high-temperature lubricating powder, flake graphite, zinc powder, copper powder, mica powder and talc powder and other ingredients, and is sintering and Prepared by high-energy ball milling, combined with base grease and rust inhibitors, it forms a thread grease with excellent performance.

Benefits of technology

This thread grease exhibits excellent anti-wear and lubrication properties under extreme pressure, significantly improves sealing performance and rust resistance, effectively prevents casing thread sticking, and is suitable for high-torque drilling conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116875358B_ABST
    Figure CN116875358B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lubricating grease, and in particular to a ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition and a preparation method thereof. The composition comprises 10-50% of base grease, 10-30% of flake graphite, 1-15% of ZrO 2 ‑MoS 2 ‑SnS 2 ‑MoDTC‑ZnO zirconium oxide ceramic-based high-temperature lubricating powder, 2‑25% zinc powder, 1‑15% copper powder, 5‑20% mica powder, 5‑15% talc powder, 0‑5% polytetrafluoroethylene and 0‑5% rust inhibitor. The sealing grease composition replaces the traditional lead powder solid filler with zirconium oxide ceramic-based high-temperature lubricating powder, and utilizes its good extreme pressure anti-wear performance, high-temperature friction reduction characteristics, rust resistance and anti-aging performance to effectively alleviate and prevent the sticking phenomenon of the casing thread sealing surface. It is particularly suitable for drilling operations with large torque such as inclined wells, horizontal wells and crossing wells, and can reduce the probability of sticking and breaking of casing threads.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lubricating grease, and particularly relates to a ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition and a preparation method thereof. Background Art

[0002] According to the definition of ISO 13679 standard, galling is a cold welding between metal surfaces in contact with each other. Galling of oil pipe threads is mainly a damage process in which the rotating surfaces of the interacting internal and external threads undergo elastic deformation, plastic deformation, extrusion and peeling, furrowing and embedding of metal under the action of friction during the process of making and breaking the oil casing. Galling is the most common form of damage and failure of various types of oil well tubing in use. In mild cases, the thread surface is damaged, affecting the ability to break the thread, requiring auxiliary disassembly or physical cutting, and reducing the service life of the oil pipe; in severe cases, leakage will occur at the threaded connection of the oil pipe, reducing the sealing performance and load-bearing capacity of the oil pipe, and even causing the accident of slipping and falling into the well, causing serious economic losses.

[0003] Because the galling is caused by the relative sliding of the metal contact surface of the oil casing thread, the quality of lubrication between the threads is an important factor affecting the galling. Thread grease is a necessary substance for connecting threads. It can not only enhance the sealing and lubricity of the oil casing threads, but also avoid the problem of over-tightening of the threads. Therefore, its application in actual work can effectively prevent the occurrence of galling. Therefore, API round thread connections must use thread sealing grease that complies with API BUL5A3. API thread sealing grease is composed of lubricating oil base grease with solid fillers such as graphite powder, aluminum, zinc, and copper. It can effectively fill the thread gap and play the dual role of long-lasting pressure-resistant sealing and thread lubricant. Lubricating oil base grease and other solid additives have lubricating effects. Their existence changes the contact surface state of the thread, improves the stress state of the thread contact surface during the process of threading and detaching, and can effectively prevent the adhesion of the thread.

[0004] However, the current API thread grease cannot fully achieve the extreme pressure and anti-wear, lubrication and friction reduction, rust prevention and sealing performance. It may still cause casing thread sticking under complex working conditions such as high-torque oil drilling. Summary of the invention

[0005] In order to solve the above problems, the present invention discloses a ceramic-based anti-seizing and anti-rusting petroleum casing thread sealing grease composition and a preparation method thereof. The thread grease provided by the present invention is developed on the basis of API thread grease. In addition to meeting all the performances of API standards, it is superior to API thread grease in extreme pressure anti-wear, lubrication and friction reduction, anti-rust and sealing performance. The thread grease provided mainly alleviates and avoids the casing thread seizing that is easy to cause under complex working conditions, so as to adapt to the high torque and sealing characteristics of the casing during drilling. .

[0006] The technical solution of the present invention is as follows:

[0007] A ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, comprising a base grease and a solid component; the mass percentage of each component is:

[0008] Base fat: 10.0-50.0%;

[0009] Solid content: 50.0-90.0%;

[0010] The solid component is composed of the following components in percentage by mass:

[0011] Zirconia ceramic-based high-temperature lubricating powder: 1.0-15.0%;

[0012] Flake graphite: 10.0-30.0%;

[0013] Copper powder: 1.0-15.0%;

[0014] Zinc powder: 5.0-25.0%;

[0015] Mica powder: 5.0-20.0%;

[0016] Talc: 5.0-15.0%;

[0017] Polytetrafluoroethylene: 0-5.0%;

[0018] Rust inhibitor: 0-5.0%;

[0019] The mass percentages of the components are the mass percentages in the sealing grease composition.

[0020] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the zirconium oxide ceramic-based high-temperature lubricating powder is a ZrO2-MoS2-SnS2-MoDTC-ZnO composite powder.

[0021] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the preparation method of the zirconium oxide ceramic-based high-temperature lubricating powder comprises the following steps:

[0022] MoS2, SnS2 and ZnO are used as solid lubricating phases, preferably with a particle size of 10-30 μm; ZrO2 powder is used as an anti-wear matrix, preferably with a particle size of 0.5-2 μm; a zirconia ceramic-based high-temperature lubricating ZrO2-MoS2-SnS2-ZnO composite material is prepared by a hot pressing sintering method, and then MoDTC (molybdenum dialkyl dithiocarbamate) is added and ground by a high-energy ball milling method to obtain a zirconia ceramic-based high-temperature lubricating powder; preferably, the zirconia ceramic-based high-temperature lubricating powder has a particle size of 10-30 μm;

[0023] Among them, the mass fraction ranges of ZrO2, MoS2, SnS2, MoDTC and ZnO are 80-90%, 2.5-7.5%, 1.5-4.5%, 1.0-3.0% and 2.5-7.5% respectively.

[0024] Preferably, the mass fractions of ZrO2, MoS2, SnS2, MoDTC and ZnO are 85.0%, 5.0%, 3.0%, 2.0% and 5.0% respectively.

[0025] Preferably, the process parameters of the pressurized hot sintering are: at 280-600°C, pressurized to 50-300Kg / cm2, and maintained for 2-4 hours.

[0026] Preferably, the process parameters of the high-energy ball milling method are grinding at a rotation speed of 200-500 r / min, a ball-to-material ratio of 10-30:1, and a ball milling time of 4-50 h.

[0027] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the base grease is an extreme pressure composite lithium-based grease, the consistency grade NLGI is grade 0, and the working cone penetration is: 355-385;

[0028] The thickener in the base fat is composed of two or more of lithium 12-hydroxystearate, dilithium sebacate, dilithium azelate or lithium borate;

[0029] The mass percentage of the thickener in the composition is 2.0-4.5%.

[0030] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the particle size of the zirconium oxide ceramic-based high-temperature lubricating powder is between 450 and 1250 meshes.

[0031] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the flake graphite particle size is between 250-360 meshes, and the carbon content is greater than or equal to 95.0%.

[0032] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the zinc powder has a particle size of 325 mesh; the copper powder, mica powder, talcum powder and polytetrafluoroethylene have a particle size of 200 mesh, and the purity of the above-mentioned components is greater than or equal to 95.0%.

[0033] Furthermore, in the above-mentioned ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the rust inhibitor is composed of calcium dinonylnaphthalenesulfonate and sorbitan monooleate in a mass ratio of 1:3-5.

[0034] Furthermore, the preparation method of the ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition comprises the following steps:

[0035] 1) preparing zirconia ceramic-based high-temperature lubricating powder, using MoS2, SnS2 and ZnO as solid lubricating phases, using zirconia powder as anti-wear matrix, and using hot pressing sintering method to prepare zirconia ceramic-based high-temperature lubricating ZrO2-MoS2-SnS2-ZnO composite material, and then adding MoDTC (molybdenum dialkyl dithiocarbamate) to grind by high-energy ball milling method, and the particle size is 10-30 μm;

[0036] 2) Prepare the materials required for the preparation of ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease in proportion;

[0037] 3) Add base grease, flake graphite, zirconium oxide ceramic-based high-temperature lubricating powder and metal powder into a stirring kettle, and stir for 40 to 120 minutes until they are completely mixed;

[0038] 4) Add mica powder, talcum powder, polytetrafluoroethylene and rust inhibitor and stir evenly, then grind again evenly with a colloid mill, a three-roll grinder or a homogenizer to obtain the thread grease of the present invention.

[0039] Furthermore, in the application of the above ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, the thread is a casing thread for drilling operations, and the well includes but is not limited to an inclined well, a horizontal well or a crossing well.

[0040] Furthermore, in the above application, the ceramic-based anti-galling and anti-rust type petroleum casing thread sealing grease is directly applied to the internal thread or external thread of the drilling casing, and then the threading can be made and broken.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1) Zirconia ceramic-based high-temperature lubricating materials and solid fillers such as graphite, zinc, and copper can effectively fill the thread gap, change the thread contact surface state, improve the thread contact surface stress state during the make-up process, and effectively prevent the thread from sticking;

[0043] 2) ZrO2-MoS2-SnS2-MoDTC-ZnO zirconium oxide ceramic-based high-temperature lubricating powder can provide more excellent anti-wear and lubrication properties at high temperature points on the rotating surfaces of internal and external threads;

[0044] 3) After the flake graphite is mixed with mica powder, talcum powder and base lubricating grease, it has good lubrication and sealing properties, chemical and solvent corrosion resistance and rust resistance. The thread sealing grease of the present invention also has rust prevention function;

[0045] The anti-sticking casing thread grease of the present invention has a black and viscous appearance and has good coating properties. It can be conveniently applied to the surface of the casing threads and plays a good anti-sticking role. The thread grease is mainly applied to the thread surface of the drill bit connection to play a lubricating and anti-sticking role. It is particularly suitable for drilling operations with large torque such as inclined wells, horizontal wells and crossing wells. It has a good effect of preventing the casing threads from sticking and wearing, and can reduce the probability of the casing threads sticking and breaking. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 Comparative diagram of oxidation stability (PDSC) test of casing thread sealing grease obtained in Examples 1-3 and Comparative Examples 1-4;

[0047] Figure 2 Extreme pressure performance (four-ball machine method) PD / N test comparison diagram of casing thread sealing grease obtained in Examples 1-3 and Comparative Examples 1-4;

[0048] Figure 3 A comparison chart of the friction coefficient (140°C, load 100N, frequency 5Hz) of the casing thread sealing grease obtained in Examples 1-3 and Comparative Examples 1-4;

[0049] Figure 4 A comparison chart of the aging test (8 cycles) of the casing thread sealing grease obtained in Examples 1-3 and Comparative Examples 1-4;

[0050] Figure 5 Comparison of the sealing test running time of the casing thread sealing grease obtained in Examples 1-3 and Comparative Examples 1-4 after the final make-up and make-out test. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.

[0053] The extreme pressure lithium composite grease in the embodiment of the present invention comes from Wuxi PetroChina Lubricating Grease Company, and the product model is: No. 0 extreme pressure lithium composite grease.

[0054] Examples 1-3

[0055] Based on 100% of the ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease, the components and weight percentages are shown in Table 1:

[0056] In the ZrO2-MoS2-SnS2-MoDTC-ZnO zirconium oxide ceramic-based high temperature lubricating powder, the mass fractions of ZrO2, MoS2, SnS2, MoDTC and ZnO are 85.0%, 5.0%, 3.0%, 2.0% and 5.0% respectively. The hot pressing sintering preparation process is: at 320℃, 70Kg / cm 2 The pressure was maintained for 2.5 hours to prepare zirconia ceramic-based high-temperature lubricating ZrO2-MoS2-SnS2-MoDTC-ZnO composite materials; then high-energy ball milling was used at a speed of 320 r / min, a ball-to-material ratio of 15:1, and a ball milling time of 6 hours to obtain a powder with a particle size of 10-30 μm.

[0057] Table 1 Group distribution ratio of Examples 1-3

[0058]

[0059] Comparative Examples 1-4

[0060] Based on 100% of the ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease, the components and weight percentages are shown in Table 2:

[0061] The content of each component and the preparation process of the ZrO2-MoS2-SnS2-MoDTC-ZnO zirconia ceramic-based high-temperature lubricating powder are completely consistent with those of the zirconia ceramic-based high-temperature lubricating powder in Examples 1-3.

[0062] Table 2 Group distribution ratio of comparative examples 1-4

[0063]

[0064] Among them, control example 4 is an API improved casing thread sealing grease prepared according to the reference standard formula in Appendix B of GB / T 23512-2015 "Evaluation and Testing of Thread Compounds for Casing, Tubing, Line Pipe and Drill String Components in the Petroleum and Natural Gas Industry".

[0065] Test Example 1

[0066] Basic physical and chemical properties test

[0067] The casing thread sealing greases obtained in Examples 1-3 and Comparative Examples 1-4 were tested for basic physical and chemical properties according to the evaluation items for thread greases for casing, oil pipes, line pipes and drill stem components in the petroleum and natural gas industry and in combination with the quality management requirements of actual production needs. The results are shown in Tables 3-4 and Attached Figure 1-4 shown.

[0068] Table 3 Analysis and test data comparison

[0069]

[0070] Table 4 Comparison of analysis and test data (continued)

[0071]

[0072]

[0073] According to Tables 3 and 4 and the attached Figure 1-4It can be seen from the data that, when the content of base grease and graphite is the same, Examples 1-3 using zirconium oxide ceramic-based high-temperature lubricating powder to replace traditional lead powder solid fillers all show excellent performance in oxidation stability, extreme pressure and wear resistance, high-temperature friction reduction characteristics and aging resistance, and have considerable performance improvement compared to Control Example 4 using traditional lead powder solid fillers. Comparing Examples 1-3, it can be found that when the total content of zinc powder and copper powder is the same, gradually increasing the content of zirconium oxide ceramic-based high-temperature lubricating powder is helpful to improve the extreme pressure, wear resistance and high-temperature friction reduction characteristics of thread grease. Comparing Example 1 containing zirconium oxide ceramic-based high-temperature lubricating powder and Control Example 1 without zirconium oxide ceramic-based high-temperature lubricating powder, it is found that: when the content of mica powder, talcum powder and polytetrafluoroethylene is the same, even if the proportion of zinc powder and copper powder is increased, Control Example 1 is inferior to Example 1 in oxidation stability, extreme pressure and wear resistance, high-temperature friction reduction characteristics and aging resistance, especially in high-temperature friction reduction characteristics. Comparing Example 3 with Control Example 2, it is found that: in the absence of mica powder and talcum powder, even if the proportion of zinc powder and copper powder is increased, Control Example 2 is inferior to Example 3 in terms of extreme pressure and wear resistance and high temperature friction reduction characteristics. By comparing Example 3 with Control Examples 2 and 3, it can be found that: when the total content of zirconium oxide ceramic-based high-temperature lubricating powder and zinc powder and copper powder is the same, compounding mica powder and talcum powder is helpful to improve the extreme pressure and wear resistance, high temperature friction reduction and rust resistance of thread grease, especially when the two are compounded in a ratio of 15:4, its comprehensive performance is significantly improved. This is mainly because zirconium oxide has excellent bending strength and fracture toughness, and its wear resistance is good. At the same time, zirconium oxide ceramic-based high-temperature lubricating powder forms molybdate (lithium molybdate, copper molybdate, zinc molybdate) under the action of the friction force on the rotating surface of the internal and external threads. Molybdate is a very good high-temperature solid lubricant. The melting point of copper molybdate is 500℃, the melting point of lithium molybdate is 705℃, and the melting point of ZrO2 is 2715℃. Therefore, ZrO2-MoS2-SnS2-MoDTC-ZnO composite lubricating material can give full play to this excellent anti-wear and lubrication performance. Flake graphite is a natural solid lubricant with a layered structure; mica powder is elastic, bendable, and has good wear resistance and abrasion resistance; talc powder has excellent physical and chemical properties such as lubricity, fire resistance, acid resistance, insulation, high melting point, chemical inactivity, softness, and strong adsorption. The crystal structure of talc is layered, so it has a tendency to split into flakes and special lubricity. The introduction of mica powder and talcum powder, and the mixing of flake graphite with mica powder, talcum powder and base grease have good lubrication, sealing and rust prevention properties, which can improve the lubrication, sealing and anti-galling properties of ceramic-based anti-galling lubricating petroleum casing thread sealing grease while further improving its rust prevention properties.

[0074] Test Example 2

[0075] Make-up and break-out test

[0076] According to ISO 13679:2002 "Test Procedures for Threaded Connections of Casing and Tubing in the Petroleum and Natural Gas Industry", the field end tubing should be tested for 9 times of make-up and make-down. When making up, the thread grease is weighed with a balance and evenly applied. The amount of thread grease used for all samples is kept consistent, and interference factors such as excessive thread grease are eliminated. Finally, the field end of the casing is made to make-up and the results are analyzed. Test of the anti-sticking properties of grease. Since industrial test methods have not reached a consensus on the anti-sticking properties of thread grease, the only reliable test method currently is to conduct a full-size API type connection thread grease anti-sticking property evaluation test (repeated make-up and make-down) in accordance with ISO13679, APIRP5C5 or GB / T 21267-2017 Test Procedures for Threaded Connections of Casing and Tubing in the Petroleum and Natural Gas Industry. During the test, the make-up speed is 20-25r / min, and the optimal torque is (1420±284)N·m.

[0077] The test objects are the sealing grease prepared in Examples 1-3 and Comparative Examples 1-4. According to the API standard, the thread should be able to withstand 9 times of threading without serious damage, so that oil field users can use it with confidence. The results are shown in Table 5 below.

[0078] Table 5 Test results of top and bottom buckles

[0079]

[0080]

[0081] After the make-up and make-up tests, different thread compounds have different sticking situations. Examples 1-3 can all withstand 9 make-up and make-up tests without serious damage. The thread compound of Example 3 has no damage to the thread after 12 make-up and make-up tests. The threads of Control Examples 1 to 3 are damaged or seriously damaged after 5 to 7 make-up and make-up tests. From the make-up and make-up test results, it can be seen that different thread compounds have different tendencies and degrees of damage to threads that stick. In the make-up and make-up test, the thread compound produced using Example 3 can not only achieve the number of make-up times required by API, but also has significantly better thread damage than other thread compounds, and has the best anti-sticking performance.

[0082] Test Example 3

[0083] Sealing test after final make-up and make-out test

[0084] The casing thread sealing grease prepared in the above Examples 1-3 and Comparative Examples 1-4 was subjected to 9 times of make-up and make-out tests according to the provisions of GB / T21267, and then the 10th make-up and casing joint air tightness test was carried out. The internal pressure was 25.0 MPa and maintained for 15 minutes to observe whether there was leakage. The results are shown in Table 6 and Table 6. Figure 5 shown.

[0085] Table 6 Airtightness test

[0086]

[0087] Test Example 4

[0088] Rust resistance test

[0089] The casing thread sealing grease obtained in the above Examples 1-3 and Control Examples 1-4 was tested for corrosion resistance and rust resistance according to the GB / T5018 grease corrosion resistance test method and the Emcor dynamic rust resistance test method to determine the rust resistance level of the grease. The test results are shown in Table 7 below.

[0090] Table 7 Corrosion and rust resistance test

[0091] GB / T5018 Corrosion resistance Emcor Dynamic Rust Resistance Example 1 qualified ≤0 / 0 Example 2 qualified ≤0 / 0 Example 3 qualified ≤0 / 0 Comparative Example 1 Unqualified (1 corrosion spot) ≤1 / 0 Comparative Example 2 qualified ≤1 / 1 Comparative Example 3 Unqualified (3 corrosion spots) ≤1 / 1 Comparative Example 4 qualified ≤1 / 0

[0092] In summary, the above embodiments illustrate that the present invention mainly utilizes the excellent bending strength, fracture toughness and wear resistance of zirconium oxide to ensure that during the process of unbuckling the oil casing, the threaded metal surface does not or reduces elastic and plastic deformation, extrusion peeling, furrowing and embedding. MoS2 and SnS2 are a kind of layered flaky material. The layers are bonded by covalent bonds or ionic bonds with strong bonding force, while the layers are bonded together by van der Waals forces with weaker bonding force. Therefore, they can easily produce relative sliding under external force operation and play a lubricating role. MoDTC reacts chemically on the surface of the friction pair, especially at the contact point with high load pressure, to promote the decomposition of organic molybdenum and decompose M O S2 and some sulfides, etc. These products are dispersed in the thread grease, adsorbed and deposited on the friction surface, thereby achieving the effects of friction reduction, anti-wear and lubrication. By taking advantage of the anti-oxidation, anti-corrosion and anti-wear properties of ZnO, adding it to the thread grease can further improve the wear resistance of the product. The sealing grease composition disclosed in the present invention replaces traditional lead powder with zirconium oxide ceramic-based high-temperature lubricating powder. The above-mentioned ZrO2-MoS2-SnS2-MoDTC-ZnO zirconium oxide ceramic-based high-temperature lubricating powder has the characteristics of excellent high-temperature lubricity, bending strength and fracture toughness, which can solve the problem of sticking caused by insufficient extreme pressure and poor lubricity during the use of casing thread sealing grease, thereby causing the pressure resistance and sealing failure of casing joints; mica powder and talcum powder are selected, and flake graphite is mixed with mica powder, talcum powder and base grease to have good lubrication, sealing and rust resistance. While improving the lubrication, sealing and anti-sticking performance of ceramic-based anti-sticking lubricating petroleum casing thread sealing grease, its rust resistance is further improved, ensuring the ductility, lubricity, sealing and corrosion and rust resistance of the grease on the rotating surfaces of internal and external threads, and effectively reducing the occurrence of sticking.

[0093] The above are only a few preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition, comprising a base grease and a solid component; characterized in that: The mass percentage of each component is: base grease: 10.0-50.0%; solid component: 50.0-90.0%; wherein the solid component is composed of the following components in mass percentage: zirconium oxide ceramic-based high-temperature lubricating powder: 1.0-15.0%; flake graphite: 10.0-30.0%; copper powder: 1.0-15.0%; zinc powder: 5.0-25.0%; mica powder: 5.0-20.0%; talc: 5.0-15.0%; polytetrafluoroethylene: 0-5.0%; rust inhibitor: 0-5.0%; the mass percentage of the components is the mass percentage in the sealing grease composition; the zirconium oxide ceramic-based high-temperature lubricating powder is ZrO2-MoS2-SnS2-MoDT C-ZnO composite powder; the preparation method of the zirconia ceramic-based high-temperature lubricating powder comprises the following steps: using MoS2, SnS2 and ZnO as solid lubricating phases and ZrO2 powder as wear-resistant matrix, adopting a hot pressing and sintering method to prepare a zirconia ceramic-based high-temperature lubricating ZrO2-MoS2-SnS2-ZnO composite material, and then adding molybdenum dialkyl dithiocarbamate MoDTC and grinding it by high-energy ball milling to obtain a zirconia ceramic-based high-temperature lubricating powder; wherein: the mass fraction ranges of ZrO2, MoS2, SnS2, MoDTC and ZnO are: 80-90%, 2.5-7.5%, 1.5-4.5%, 1.0-3.0%, 2.5-7.5% respectively.

2. A ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to claim 1, characterized in that: The base grease is an extreme pressure composite lithium-based grease with a consistency grade NLGI of 0 and a working cone penetration of 355-385; the thickener in the base grease is composed of a combination of two or more of 12-hydroxystearate lithium, dilithium sebacate, dilithium azelaate or lithium borate; the mass percentage of the thickener in the composition is 2.0-4.5%.

3. A ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to claim 1, characterized in that: The particle size of the zirconium oxide ceramic-based high-temperature lubricating powder is between 450 and 1250 meshes.

4. The ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to claim 1, characterized in that: The flake graphite has a particle size between 250-360 meshes and a carbon content greater than or equal to 95.0%.

5. The ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to claim 1, characterized in that: The zinc powder has a particle size of 325 meshes; the copper powder, mica powder, talcum powder and polytetrafluoroethylene have a particle size of 200 meshes, and the purity of the above components is greater than or equal to 95.0%.

6. The ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to claim 1, characterized in that: The rust inhibitor is composed of calcium dinonylnaphthalenesulfonate and sorbitan monooleate in a mass ratio of 1:3-5.

7. A method for preparing a ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) Prepare zirconia ceramic-based high-temperature lubricating powder, take MoS2, SnS2 and ZnO as solid lubricating phase, take zirconia powder as anti-wear matrix, adopt hot pressing sintering method to prepare zirconia ceramic-based high-temperature lubricating ZrO2-MoS2-SnS2-ZnO composite material, then add dialkyl dithiocarbamate molybdenum MoDTC and grind it by high-energy ball milling method, and the particle size is 10-30μm; 2) Prepare various materials required for the preparation of ceramic-based anti-seizing and anti-rust petroleum casing thread sealing grease in proportion; 3) Add base grease, flake graphite, zirconia ceramic-based high-temperature lubricating powder and metal powder into a stirring kettle, start stirring for 40-120 minutes, until completely mixed; 4) Add mica powder, talc powder, polytetrafluoroethylene and rust inhibitor, stir evenly, and grind it again with a colloid mill, a three-roll grinder or a homogenizer to obtain a ceramic-based anti-seizing and anti-rust petroleum casing thread sealing grease composition.

8. Application of a ceramic-based anti-galling and anti-rust petroleum casing thread sealing grease composition as claimed in any one of claims 1 to 6, characterized in that: The thread is a casing thread for drilling operations, and the well includes but is not limited to an inclined well, a horizontal well or a crossing well.

Citation Information

Patent Citations

  • Water-resistant oleosol and method of producing the same

    CN101153236A

  • API oil sleeve thread sealing grease composite and preparation method thereof

    CN101565648A

  • ZrO2-MoS2-CaF2 high-temperature self-lubricating wear-resistant material

    CN105294099A